Lactose-free milk prolonged endurance capacity in lactose intolerant Asian males - Sudsa-ard, Kriyot (2015)
Background: Several studies on Caucasian volunteers have proven that milk is an effective recovery drink for athletes. Such benefit, however, cannot be directly applied to the lactose-intolerant Asian population. This study investigated the effects of ingesting water (WT), sports drink (SPD) and lactose-free milk (LFM) on cycling capacity. Methods: Ten healthy young men completed 3 randomized experimental trials. Each trial consisted of an intermittent glycogen depleting session, a 2 h recovery period during which they ingested the test drink, followed by cycling at 70% of their maximum oxygen consumption (VO2max) to volitional exhaustion. Each trial was separated by at least one week. Results: There were no complaints or symptoms of lactose intolerance during any of the trials. The cycling periods were different (p < 0.05) amongst the 3 trials, namely, lactose-free milk (LFM; 69.6 ± 14.0 min), sports drink (SPD; 52.1 ± 11.6 min), and water (WT; 36.0 ± 11.1 min), respectively. The VO2 and VCO2 of LFM (30 ± 4 and 29 ± 4 ml/kg/min) were lower (p < 0.05) than that of SPD (34 ± 4 and 34 ± 4 ml/kg/min) and WT (35 ± 4 and 33 ± 5 ml/kg/min). There were no differences (p = 0.45) in VO2 and VCO2 between SPD and WT. Mean rating of perceived exertion was lowest in LFM (14 ± 5; p < 0.05), while no difference was found between the other two trials (SPD: 16 ± 4 and WT: 16 ± 4; p = 0.18). Conclusion: Lactose-free milk is likely to be an effective recovery drink for enhancing subsequent cycling capacity in lactose intolerant Asian males.